Design, construction and evaluation of a dual device with cellular / satellite coverage for mobile asset tracking technology transfer through (2015)
This paper presents the design, construction and evaluation of the wireless device OSP cellular and satellite coverage for localization and tracking of mobile assets in Colombia (public transport, freight, carriers, etc.). The development of this product integrates hardware, software and communications interfaces, and it is aligned with a need identified in the market by the company One Solution Position: OSP LTD. With this technology transfer is to improve in offering wireless services for mobile asset tracking using a dual cellular/satellite, versatile, economical, low-power, limited only international standards FCC and CE Mark.